The Application Of Linguistic Landscape In Mataram City Kota Madya Mataram, West Nusa Tenggara Province, Indonesia - Jupri, Jupri; Aprianoto, Aprianoto; Firman, Edi (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This research investigated; the language and how the languages are used in the official and unofficial spaces of the linguistic landscape in Mataram city, West Nusa Tenggara Province; the motive of the use of both monolingual and bilingual language on the use of linguistic landscapes; the contribution to the enrichment of landscape linguistic studies. This research used qualitative study which aims at describing the results of linguistic landscape analisys to find the structure of language use on monolingualism and bilingualism and the motive of language use. The researcher found that the use of top-down pattern shows a usage of monolingualism and bilingualism of Bahasa Indonesia, English, Arabic and Balinese language, while the bottom-up pattern indicates a monolingual and bilingual pattern in Bahasa Indonesia, English, Arabic and Balinese language. The researcher also found the motives for the appearance of language codes in landscape linguistics demonstrates three factors pursuant to the concept of Gorter (2006); language revitalization including national languages as official language, language preservation, and historical; markers of globalization including modernization, branding strategies, expansion strategies, cultural introduction, identity existence includes cultural recognition, cultural preservation, branding strategy, and community formation.